Structural and vascular features in cavitary congenital optic disc anomaly associated with metaphyseal acroscyphodysplasia. Issue 4 (July 2022) - Fossataro, Federica; D'Andrea, Luca; Cennamo, Gilda
Purpose: To evaluate the radial peripapillary vascular plexus of a cavitary congenital optic disc anomaly in a young patient with recessive autosomal metaphyseal acroscyphodysplasia using optical coherence tomography angiography (OCTA). Methods: Observational case report. Results: A 17-year-old man, with diagnosis of metaphyseal acroscyphodysplasia was referred to Eye Clinic for fundus examination and multimodal imaging for retinal epithelium hypertrophy in the right eye. Clinical examination showed cup-shaped metaphyses, short stature, hyperthelorism, and telecanthus. An optic disc coloboma was detected in the right eye on fundus examination. Wide field en-face Optical Coherence Tomography (OCT) showed a hyporeflective area corresponding to the right optic disc coloboma. At OCTA examination, the whole papillary region revealed a rarefaction of the vascular network, while the ganglion cell complex's and retinal fiber layers' parameters were normal in both eyes. Conclusion: The presence of coloboma disc congenital defect linked to embryological abnormalities during the development process could pave the way for a wider understanding of the pathogenesis of metaphyseal acroscyphodysplasia by increasingly framing it as a systemic disease.